Effects of hybridization on the tension–tension fatigue behavior of continuous-discontinuous fiber-reinforced sheet molding compound composites. (August 2022) - Bartkowiak, M.; Liebig, W.V.; Montesano, J.; Weidenmann, K.A.
Highlights: Continuous-discontinuous sheet molding compounds show excellent fatigue properties. Hybridization effects are stronger under fatigue than under monotonic loading. Constraining effects lead to a higher fatigue strength of the continuous plies. A cross-ply continuous reinforcement leads to an unfavorable damage evolution. The S-N behavior of hybrid SMC can be approximated from the behavior of DiCo SMC. Abstract: This study is focused on the fatigue of sheet molding compounds (SMC) with a discontinuous (DiCo) glass fiber-reinforced core and continuous (Co) unidirectional ([0/DiCo/0]) or cross-ply ([0/90/DiCo/90/0]) carbon fiber-reinforced face layers. Tension-tension tests were conducted on the constituents (i.e., DiCo and Co SMC) and hybrid specimens. Hybridization effects were larger under cyclic than under monotonic loading. Constraining effects resulted in enhanced high fatigue strength of the Co plies in [0/DiCo/0]. [0/90/DiCo/90/0] was more sensitive to fatigue than [0/DiCo/0] due to localized damage starting from 90°-ply cracks. The S-N behavior of the hybrid was approximated from the behavior of DiCo SMC.